La práctica de la evaluación del riesgo de violencia en España - Arbach Lucioni, K. (2015)
Background. Violence risk assessment is a key requirement in professional decision making involving prevention, intervention or reporting on human behavior. The use of structured tools for violence risk assessment has shown to improve the accuracy of assessments based exclusively on clinical judgment or expertise in psychiatric, correctional and legal settings. Objectives. This study presents results of the first survey about professional practices associated with tools for violence risk assessment in Spain. Materials and methods. The information was collected by administering an online-based survey that was distributed by e-mail to members of professional organizations around the country. Results. As in professional contexts worldwide, the Robert Hare’s psychopathy scales (Psychopathy Checklist-Revised and Psychopathy Checklist: Screening Version) and the Historical-Clinical-Risk Management-20 topped the list of the most used tools both by professional choice and institutional requirement. Conclusions. We provide novel data on the prevalence of use and the perceived utility of specific tools, as well as on other issues related to the professional practice of violence risk assessment in Spain, which can guide professional in the health care, correctional and forensic settings, as well as those responsible for decisions in institutions about choosing which tool to implement.